Paper presented at the Professional Lecture "Managing Information in Specialized Areas in Costa Rica" - Miranda Arguedas, Alice (1992)
In the Cycle of Professional Conferences, Director Alice Miranda Arguedas of the School of Library, Documentation and Information of the National University presents her paper with the theme "Information Management in Specialized Areas in Costa Rica".